If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3 + -2x) = 10(4 + -2x) + -85 (3 * 5 + -2x * 5) = 10(4 + -2x) + -85 (15 + -10x) = 10(4 + -2x) + -85 15 + -10x = (4 * 10 + -2x * 10) + -85 15 + -10x = (40 + -20x) + -85 Reorder the terms: 15 + -10x = 40 + -85 + -20x Combine like terms: 40 + -85 = -45 15 + -10x = -45 + -20x Solving 15 + -10x = -45 + -20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20x' to each side of the equation. 15 + -10x + 20x = -45 + -20x + 20x Combine like terms: -10x + 20x = 10x 15 + 10x = -45 + -20x + 20x Combine like terms: -20x + 20x = 0 15 + 10x = -45 + 0 15 + 10x = -45 Add '-15' to each side of the equation. 15 + -15 + 10x = -45 + -15 Combine like terms: 15 + -15 = 0 0 + 10x = -45 + -15 10x = -45 + -15 Combine like terms: -45 + -15 = -60 10x = -60 Divide each side by '10'. x = -6 Simplifying x = -6
| 4(x-10)=5x-45 | | 2x-5x-2=-3+4x-43 | | y=-1+-0.1666666667x | | IV=ir | | a^4-1698a-2704=0 | | 88-6x=-10x+85 | | -46-8x=5(-7x+7) | | 3=5-2 | | 75+10=15h | | 2(1.5)-3y=2 | | 4u-6=-2 | | p-0.30p=25.20 | | -20=4w | | 8x+6x-20=60-6x | | 7x+4q=8+3q | | 2(y)+8=8 | | y=x^3-6x^2-36x+15 | | 8=0.25(-m-1) | | 3(-3+2x)=9 | | 3m+n=35 | | 3(x+1)+2(2x-6)=33 | | 3x^3+2x^2+-41x+-66=0 | | 8a-48=-6(-6-6a) | | 6(2-3x)=4(5x+7) | | 2(5*555*5)-56= | | 5y+60-9=12+8y-72 | | 200*50+20= | | 9m+5=9m+6 | | m=n-7 | | -34m=12 | | 2x-9y=-3 | | 0=12x+4.9x^2 |